2014
DOI: 10.1007/s10596-013-9399-2
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-based hierarchical multi-objective production optimization of smart wells

Abstract: In an earlier study two hierarchical multi-objective methods were suggested to include short-term targets in life-cycle production optimization. However this earlier study has two limitations: 1) the adjoint formulation is used to obtain gradient information, requiring simulator source code access and an extensive implementation effort, and 2) one of the two proposed methods relies on the Hessian matrix which is obtained by a computationally expensive method. In order to overcome the first of these limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…The gradient is used in a simple steepest ascent scheme, where we determine the step size with the aid of an inexact line search and the Arjimo conditions (Nocedal and Wright 2006). We use the switching approach for hierarchical multi-objective optimization with implementation details as described in Fonseca et al (2014 …”
Section: Numerical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…The gradient is used in a simple steepest ascent scheme, where we determine the step size with the aid of an inexact line search and the Arjimo conditions (Nocedal and Wright 2006). We use the switching approach for hierarchical multi-objective optimization with implementation details as described in Fonseca et al (2014 …”
Section: Numerical Examplementioning
confidence: 99%
“…In Stordal et al (2014) it is shown how this implementation converges to the exact gradient in a natural evolutionary framework. Fonseca et al (2014) investigated the applicability of EnOpt for multi-objective optimization based on a single model realization and showed results which suggest that EnOpt is a viable alternative when the adjoint is unavailable. Furthermore, the robust EnOpt implementation as introduced by Chen et al (2008), which uses a 1:1 ensemble ratio, is computationally competitive to the adjoint method, because one adjoint simulation is required for each model realization.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is, in theory, also possible to implement our method using approximate gradients obtained with, e.g. the simultaneous perturbation stochastic approximation (SPSA) technique (see [19]) or ensemble optimization (EnOpt) (see [3] for the basics of the method and [8] for an implementation in hierarchical optimization). The latter (EnOpt) approach also allows for the inclusion of uncertainty in the reservoir models; see [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we note that other weak-constrained optimization methods could be applied to solve the hierarchical optimization problem. The current implementation has shown to be robust in various applications using both adjoint-based and ensemble-based techniques [4,8,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation